2011
DOI: 10.1053/j.gastro.2011.06.063
|View full text |Cite
|
Sign up to set email alerts
|

Host Response to Translocated Microbial Products Predicts Outcomes of Patients With HBV or HCV Infection

Abstract: Background & Aims Chronic infection with hepatitis B or C virus (HBV or HCV) is a leading cause of cirrhosis, by unknown mechanisms of pathogenesis. Translocation of gut microbial products into the systemic circulation might increase because of increased intestinal permeability, bacterial overgrowth, or impaired clearance of microbial products by Kupffer cells. We investigated whether the extent and progression of liver disease in patients with chronic HBV or HCV infection are associated with microbial translo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
258
10
13

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(308 citation statements)
references
References 59 publications
20
258
10
13
Order By: Relevance
“…First, Sandler et al demonstrated elevated levels of sCD14 in hepatitis B virus (HBV) and HCV patients with severe fibrosis and reported a prognostic value for CD14 1 macrophages and sCD14 for disease progression in chronic viral hepatitis. 5 However, this is in contrast with the findings of Kuniholm et al In a recent study from our group, HCV patients with cirrhosis, as assessed by transient elastography, had higher levels of sCD163 and sCD206 (the shed mannose receptor), compared to those with no/mild fibrosis. However, sCD206 was inferior to sCD163 in cirrhosis prediction, 6 supporting the notion that sCD163 may be the best macrophagespecific biomarker in chronic viral hepatitis.…”
Section: Replycontrasting
confidence: 98%
“…First, Sandler et al demonstrated elevated levels of sCD14 in hepatitis B virus (HBV) and HCV patients with severe fibrosis and reported a prognostic value for CD14 1 macrophages and sCD14 for disease progression in chronic viral hepatitis. 5 However, this is in contrast with the findings of Kuniholm et al In a recent study from our group, HCV patients with cirrhosis, as assessed by transient elastography, had higher levels of sCD163 and sCD206 (the shed mannose receptor), compared to those with no/mild fibrosis. However, sCD206 was inferior to sCD163 in cirrhosis prediction, 6 supporting the notion that sCD163 may be the best macrophagespecific biomarker in chronic viral hepatitis.…”
Section: Replycontrasting
confidence: 98%
“…Similarly, for 98 HIV/HCV coinfected patients on virologically suppressive ART, we reported increased sCD14 levels in subjects either harboring aggressive HCV genotypes (i.e., genotypes 1 to 4) or presenting with cirrhosis (129). Furthermore, Sandler et al reported that higher sCD14 levels distinguish patients with severe liver fibrosis from those with minimal fibrosis in a cohort of hepatitis B virus (HBV)/HCV-monoinfected subjects (130). These results suggest a pathogenic role of the host response to LPS in severe HIV/HCV-related liver disease.…”
Section: Microbial Translocation In Liver Diseasesupporting
confidence: 52%
“…Although several factors have been associated with the response to anti-HCV therapy, the determinants of successful full-course peg-IFN-␣-ribavirin therapy are still poorly defined (133)(134)(135)(136)(137). Interestingly, increased plasma sCD14 levels have been proven to be independently associated with poor responses to anti-HCV treatment (129,130), thus suggesting an independent role of microbial translocation in the outcome of anti-HCV therapy. Contrasting data, however, were obtained for a cohort of ART-naïve HIV/ HCV-coinfected patients with high CD4 ϩ T-cell counts, for whom higher sCD14 levels were independently associated with a decreased risk of liver disease progression, defined as a time to Fibrosis 4 (Fib-4) score of Ͼ1.45 or liver-related death.…”
Section: Microbial Translocation In Liver Diseasementioning
confidence: 99%
“…5 However, this is in contrast with the findings of Kuniholm et al In a recent study from our group, HCV patients with cirrhosis, as assessed by transient elastography, had higher levels of sCD163 and sCD206 (the shed mannose receptor), compared to those with no/mild fibrosis. However, sCD206 was inferior to sCD163 in cirrhosis prediction, 6 supporting the notion that sCD163 may be the best macrophagespecific biomarker in chronic viral hepatitis.…”
contrasting
confidence: 98%